2017
DOI: 10.1016/j.clinph.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of short-term plasticity in the dorsolateral prefrontal cortex with theta burst stimulation: A TMS-EEG study

Abstract: TBS is able to modulate cortical reactivity and cortical inhibition in the prefrontal cortex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
89
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 79 publications
19
89
5
Order By: Relevance
“…In addition, the N100 deflection is considered to have a high sensitivity to small changes in cortical excitability compared with other TEPs (Nikulin, Kicic, Kahkonen, & Ilmoniemi, 2003), making it an ideal candidate for tracking neuromodulatory paradigms. Studies have reported N100 to be associated with GABA B -mediated inhibitory mechanisms in both motor (Bonnard et al, 2009;Farzan et al, 2013;Premoli, Rivolta, et al, 2014b;Rogasch, Daskalakis, et al, 2013a) and prefrontal cortex (Chung et al, 2017;Rogasch et al, 2015). The amplitude of N100 increased following SAI both in motor and prefrontal cortex (Noda et al, 2016;Noda, Zomorrodi, Backhouse, et al, 2017c), but decreased following cerebellar iTBS (Casula, Pellicciari, Ponzo, et al, 2016b), which are in line with the change observed in N100 following Ind iTBS.…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prsupporting
confidence: 74%
See 4 more Smart Citations
“…In addition, the N100 deflection is considered to have a high sensitivity to small changes in cortical excitability compared with other TEPs (Nikulin, Kicic, Kahkonen, & Ilmoniemi, 2003), making it an ideal candidate for tracking neuromodulatory paradigms. Studies have reported N100 to be associated with GABA B -mediated inhibitory mechanisms in both motor (Bonnard et al, 2009;Farzan et al, 2013;Premoli, Rivolta, et al, 2014b;Rogasch, Daskalakis, et al, 2013a) and prefrontal cortex (Chung et al, 2017;Rogasch et al, 2015). The amplitude of N100 increased following SAI both in motor and prefrontal cortex (Noda et al, 2016;Noda, Zomorrodi, Backhouse, et al, 2017c), but decreased following cerebellar iTBS (Casula, Pellicciari, Ponzo, et al, 2016b), which are in line with the change observed in N100 following Ind iTBS.…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prsupporting
confidence: 74%
“…The amplitude of N100 increased following SAI both in motor and prefrontal cortex (Noda et al, 2016;Noda, Zomorrodi, Backhouse, et al, 2017c), but decreased following cerebellar iTBS (Casula, Pellicciari, Ponzo, et al, 2016b), which are in line with the change observed in N100 following Ind iTBS. However, our previous studies showed increased N100 following prefrontal iTBS (50 Hz at 5 Hz) (Chung et al, 2017;Chung, Rogasch, Hoy, & Fitzgerald, 2018a;Chung, Rogasch, Hoy, Sullivan, et al, 2018b), and the discrepancy of the outcome…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prmentioning
confidence: 82%
See 3 more Smart Citations